A STUDY OF EUPHEMISM USED BY PRESIDENT BARACK OBAMA IN THE FIRST INAUGURAL ADDRESS - MUSFIROH, UCI NURIL (Jurnal Ilmiah Mahasiswa FIB, 2014)
Musfiroh, Uci Nuril. 2013.  A Study of Euphemism Used by President Barack Obama in the First Inaugural Address.  Study Program of English, Faculty of Cultural Studies, Department of Language  and Literature Universitas Brawijaya,Supervisor: Isti Purwaningtyas; Co-Supervisor: Didik Hartono.Key words: Sociolinguistics, euphemism, speech, President Barack ObamaAs human being, we must understand about communication and its function for daily life. It could be meaningful  if it is done by two or group of people. Language is a best tool to conduct communication in order to show ideas and emotion. In fact language affects speech norms of a particular community, it depends on how the society using language. In this study the writer is interested in analyzing euphemism, it is about using mild language to prevent the harsh language in particular terms. The writer examines euphemistic expressions used by President Barack Obama in inaugural address. This study attempts to answer the two research problems, namely: (1) what are types of euphemism used by President Barack Obama in his inauguration speech, and (2) what are motives of President Barack Obama in using euphemisms in his inauguration address. In analyzing the types of euphemism in  this study, the writer uses the theory of Beatrice Warren (1992). She gives four devices for euphemism formation: word formation devices, phonemic  modification, loan words, and semantic innovation. Later in analyzing motives in using euphemism, the writer uses theory of Stephen Ullman (1962) where he has three categories of euphemism motives: fear, delicacy fall and propriety. This study uses a qualitative approach to analyze the data in form of transcript that containing euphemistic expression used by Obama. In the result shown in the transcript proved that Obama used several types of euphemism: 2 compounding, 8 implication, 23 metaphor, 8 metonym, and 2 reversal. In addition, the analysis of motives in  using euphemistic expressions found in the inaugural address transcript is 18 motives of delicacy fall, and 25 motives propriety. The study is expected to be useful  for student who concerns in English language and literature department and certainly for students who focus on euphemism research. Through this study, the writer also hopes that this study can help the next researcher to develop this research by using a different object.